Determinants of Dividend Policy: An Empirical Analysis of UK London Stock Exchange FTSE 350 - Cheng, Wen (2009)
Abstract This paper investigates the determinants of dividend policy of London Stock Exchange FTSE 350, which uses a firm-level panel data set of FTSE350 during the period 1993 to 2008. Eight research hypotheses are employed, which derived from the main theories of corporate dividend policy to examine the determinants. Both dynamic panel data model and static panel data model are used to test the determinants of dividend policy. Dynamic panel data model is used to test Lintner‟s model (1956). We find that although there are limitations in Lintner‟s model, the main determinants, i.e. past dividends and current earnings are derived from his model which also influences modern corporate dividend policy. Static panel data model is also utilized. The results suggest that: a) profitability, growth opportunities, firm size and taxation are main determinants of corporate dividend policy; b) The findings support signalling theory and agency theory; c) There is no relevance between financial leverage and dividend policy.